2011
DOI: 10.1088/0967-3334/32/12/001
|View full text |Cite
|
Sign up to set email alerts
|

On the shape of the common carotid artery with implications for blood velocity profiles

Abstract: Clinical and engineering studies typically assume that the common carotid artery (CCA) is straight enough to assume fully developed flow, yet recent studies have demonstrated the presence of skewed velocity profiles. Towards elucidating the influence of mild vascular curvatures on blood flow patterns and atherosclerosis, the present study aimed to characterize the three-dimensional shape of the human CCA. The left and right carotid arteries of 28 participants (62±13 years) in the VALIDATE (Vascular Aging – The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…4,17,43 Previous studies on the geometric characterization of CCA compare favorably with our results reported in Table 3 and in Fig. 5, e.g., Tortoli et al 44 reported a curvature varying from 0.0025 to 0.01 mm 21 and Manbachi et al 23 reported an average thoracic CCA curvature of 0.007 ± 0.004 mm 21 . Furthermore, as described by Manbachi et al, 23 the CCA geometry can be divided into thoracic and cervical portions, the thoracic CCA segment being significantly more curved that the cervical segment.…”
Section: Cca3-cca11supporting
confidence: 90%
See 2 more Smart Citations
“…4,17,43 Previous studies on the geometric characterization of CCA compare favorably with our results reported in Table 3 and in Fig. 5, e.g., Tortoli et al 44 reported a curvature varying from 0.0025 to 0.01 mm 21 and Manbachi et al 23 reported an average thoracic CCA curvature of 0.007 ± 0.004 mm 21 . Furthermore, as described by Manbachi et al, 23 the CCA geometry can be divided into thoracic and cervical portions, the thoracic CCA segment being significantly more curved that the cervical segment.…”
Section: Cca3-cca11supporting
confidence: 90%
“…5 Our quantitative findings enforce and widen recent evidences of complex non-axisymmetric flow fields in CCA. 9,14,23,35,44 With respect to full-length models, incorporating both the thoracic and the cervical CCA, the amount of helical flow in the carotid bifurcation can be reasonably captured if the CCA is extended until the CCA7 location. It is general practice, in computational hemodynamic studies of the carotid bifurcation, the assumption that CCA is nominally straight to justify the adoption of classical theories valid for long straight tubes (e.g., Womersley theory) for the prescription of (Dirichlet) conditions at the inflow boundaries of the fluid domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B). The relative orientation of two subsequent best-fit planes was expressed by a tilt ( α) and a twist ( θ ) angle, calculated as the arccosine of the internal product between the two tangent vectors and the two normal vectors, respectively [36] . Moreover, twist angle can be related to Euler's rotation theorem, stating that a rotation in the 3D space can be expressed as a single rotation around an axis, which is invariant to the rotation.…”
Section: Morphometric Characterizationmentioning
confidence: 99%
“…Many studies on shear stress have relied on the assumption that increased flow rates result in increased shear stress (Milkiewicz et al, 2001;Ziada et al, 1989). Though this is a valid assumption for straight, unbranched blood vessels, shear stress levels cannot be calculated purely based on the flow rate for more complex geometries (Manbachi et al, 2011). In these more complicated situations, calculation of shear stress levels requires solving a set of partial differential equations, called the Navier-Stoke's equation, for each specific geometry.…”
Section: Introductionmentioning
confidence: 99%